2017
DOI: 10.1002/anie.201710185
|View full text |Cite
|
Sign up to set email alerts
|

“Head‐to‐Middle” and “Head‐to‐Tail” cis‐Prenyl Transferases: Structure of Isosesquilavandulyl Diphosphate Synthase

Abstract: We report the first X-ray crystallographic structure of the "head-to-middle" prenyltransferase, isosesquilavandulyl diphosphate synthase, involved in biosynthesis of the merochlorin class of antibiotics. The protein adopts the ζ or cis-prenyl transferase fold but remarkably, unlike tuberculosinol adenosine synthase and other cis-prenyl transferases (e.g. cis-farnesyl, decaprenyl, undecaprenyl diphosphate synthases), the large, hydrophobic side chain does not occupy a central hydrophobic tunnel. Instead, it occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 20 publications
1
25
0
Order By: Relevance
“…8 The chemical structures of their substrates (dimethylallyl diphosphate 4 , and geranyl diphosphate 5 ) and products ( 1–3 ) are shown in Scheme 1b, and the X-ray structures of LPPS, CLDS and Mcl22 have recently been reported. 911 The mechanisms of action of LPPS and Mcl22 involve ionization (or at least partial charge separation if the mechanism is concerted 4 ) of a dimethylallyl diphosphate (DMAPP, 4 ) in the allylic S1 site followed by condensation with either 4 or 5 in the S2 site to form 1 or 2 , and this mechanism is quite similar to that reported 12 for undecaprenyl diphosphate synthase, UPPS. The mechanism of action of CLDS which forms cyclo -LPP ( 3 ) and not LPP is more complex since it involves an intermediate cyclization reaction, but in very recent work, Tomita et al 10 proposed an elegant mechanism involving a proton shift leading to a carbocation rearrangement, Scheme 2, based on isotope labeling, crystallography and computational docking.…”
Section: Introductionsupporting
confidence: 54%
See 1 more Smart Citation
“…8 The chemical structures of their substrates (dimethylallyl diphosphate 4 , and geranyl diphosphate 5 ) and products ( 1–3 ) are shown in Scheme 1b, and the X-ray structures of LPPS, CLDS and Mcl22 have recently been reported. 911 The mechanisms of action of LPPS and Mcl22 involve ionization (or at least partial charge separation if the mechanism is concerted 4 ) of a dimethylallyl diphosphate (DMAPP, 4 ) in the allylic S1 site followed by condensation with either 4 or 5 in the S2 site to form 1 or 2 , and this mechanism is quite similar to that reported 12 for undecaprenyl diphosphate synthase, UPPS. The mechanism of action of CLDS which forms cyclo -LPP ( 3 ) and not LPP is more complex since it involves an intermediate cyclization reaction, but in very recent work, Tomita et al 10 proposed an elegant mechanism involving a proton shift leading to a carbocation rearrangement, Scheme 2, based on isotope labeling, crystallography and computational docking.…”
Section: Introductionsupporting
confidence: 54%
“…Figure 3 shows a sequence alignment of CLDS together with six other ζ-fold proteins: CLDS, Mcl22, LPPS, a tomato cis -farnesyl diphosphate synthase (FPPS), E. coli undecaprenyl diphosphate synthase (UPPS), Mycobacterium tuberculosiscis -FPPS (Rv1086c), and M. tuberculosis decaprenyl diphosphate synthase (Rv2361c). Figure 4 shows structural alignments between CLDS and these 6 proteins 911, 22,23 and Figure 5a shows an alignment of the ligands and residues of mechanistic interest. All proteins have similar ζ-folds 3 with, on average, a 1.842 A Cα rmsd between CLDS and the six other proteins.…”
Section: Resultsmentioning
confidence: 99%
“…It catalyzes the head‐to‐middle (i.e., non–head‐to‐tail) condensation reaction of the C2–C3 double bond of the first allylic substrate (located at S2 site) and C1 in a second allylic substrate (located at S1 site), subsequently producing branched mono‐ or sesquiterpenes (Figure 6a). Some well‐known examples are 10‐carbon lavandulyl diphosphate (LPP), catalyzed by lavandulyl diphosphate synthase (LPPS) or Z,Z‐farnesyl diphosphate synthase (zFPS) 86,87 ; 10‐carbon cyclolavandulyl diphosphate (CLPP), catalyzed by cyclolavandulyl diphosphate synthase (CLPPS) 88 ; 15‐carbon isosesquilavandulyl diphosphate (ISLPP), catalyzed by isosesquilavandulyl diphosphate synthase (Mcl22) 89 ; and 20‐carbon geranyl lavandulyl diphosphate (GLPP), catalyzed by MA1831, a cis ‐prenyltransferase homologue from Methanosarcina acetivorans (Figure 6b–f). 90 …”
Section: Class 3: Head‐to‐middle Prenyl Synthasementioning
confidence: 99%
“…X‐ray crystallography analyses have revealed that the protein structures of UPP synthase (UPPS), LPPS, CLDS, and Mcl22 adopt a typical fold for the cis ‐type IDS family (Figure ). These structures have allowed mechanistic and structural comparison among the cis ‐type IDS homologous enzymes.…”
Section: Coupling Mechanismmentioning
confidence: 99%